Development of an innovative model for the inter-integration of the architecture of the intelligent computer environment of critical infrastructure facilities of the railway - Holub, Halyna; Gorobchenko, Olexsandr; Kulbovskyi, Ivan; Goolak, Sergey; Haidenko, Oles (Technology audit and production reserves, 2023)
The object of research is the processes of intelligent management of the computer environment of data objects of the critical infrastructure of railway transport. When developing an innovative model of deep mutual integration of the architecture of an intelligent computer environment for the management of objects in the power supply system of railway transport, the only urgent task is to solve the problems of efficient and reliable power supply of electricity for train traction to ensure the transportation process. The approaches, mathematical models and methods that became the basis for the creation of an innovative model and a new structure of the management system, the integration of the architecture of the computer environment of data of critical objects of the infrastructure of railway transport, meet the requirements of modernity and the strategy of sustainable development of the transport infrastructure. Management of an intelligent computer environment in the context of the railway power supply system is a complex process that includes the use of various technologies and strategies to optimize the functioning of systems, increase reliability, ensure efficient use of electricity, and ensure the transportation process. The basis of the creation of an intelligent computer environment is the principle of a single informational and synchronous space for the formation of primary information, which is an important concept in the development of intelligent control systems for the power supply system of railway transport. This principle requires that all parameters and data that are collected from different systems of power supply facilities should be combined in a single information space and be available for analysis and management in real time. This principle creates the basis for innovative solutions in the field of railway power supply system management, and the use of the Internet of Things, artificial intelligence, machine learning and deep learning allows the development of systems that meet modern requirements for the efficiency and reliability of energy systems. The use of the approach of deep mutual integration of the architecture of the computer environment is key in the possibility of automating the processes of data collection and analysis, as well as in improving the interaction between the components of the systems of power supply facilities of railway transport, the reliability and efficiency of the system, which makes it more flexible and adaptive to changes in load and working conditions. The research presented in the work can be used in practice in organizations, structural units and at the levels of the management system of critical infrastructure objects in railway transport, transport sector enterprises, which will allow a quick response to an emergency situation and switch to backup modes, ensuring reliability and availability of power supply in conditions of challenges.